Optimizing The Role Of Artificial Intelligence Technology In The Prevention And Enforcement Of Criminal Law: An Indonesian Legal Perspective - Ramadhany Nasution (Jurnal Multidisiplin Sahombu, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the Indonesian criminal law system. This research aims to examine the implementation of AI in the prevention and enforcement of criminal law, with a focus on normative juridical analysis of the integration of advanced technology in the justice system. The research method uses a normative juridical approach through literature study. Data were collected from primary and secondary legal sources and literature related to the implementation of AI in criminal law. Data analysis was conducted qualitatively to explore the potential and challenges of using AI. The results showed that AI has significant potential to increase the effectiveness of crime prevention through predictive analysis and law enforcement through digital evidence processing. This technology can help identify criminal patterns, track criminals, and support judicial administrative processes. However, its implementation requires a comprehensive regulatory framework to address ethical issues, privacy, and potential algorithm bias. The research identified the need for human resource development and adaptation to the local cultural context. Conclusions emphasize AI as a support tool, not a replacement for the justice system. It has the potential to improve efficiency, but cannot replace moral considerations and human conscience in upholding justice.